Improving proprioceptive deficits after stroke through robot-assisted training of the upper limb: a pilot case report study. Issue 2 (3rd March 2016) - Colombo, R.; Sterpi, I.; Mazzone, A.; Delconte, C.; Pisano, F.
ABSTRACT: The purpose of this study was to determine whether a conventional robot-assisted therapy of the upper limb was able to improve proprioception and motor recovery of an individual after stroke who exhibited proprioceptive deficits. After robotic sensorimotor training, significant changes were observed in kinematic performance variables. Two quantitative parameters evaluating position sense improved after training. Range of motion during shoulder and wrist flexion improved, but only wrist flexion remained improved at 3-month follow-up. These preliminary results suggest that intensive robot-aided rehabilitation may play an important role in the recovery of sensory function. However, further studies are required to confirm these data.